Respostas das citocinas após diferentes corridas: Revisão sistemática - Rodolpho, S. G. L.; Lopes, J. S. S.; Gonçalves, L. C. O.; de Abreu Verli, M. V.; Pérego, S. M.; de Magalhães Neto, A. M. (Revista Brasileira de Medicina do Esporte, 2024)
Introduction: In the sports universe, cytokine analyses in response to running are implemented as a strategy to support training dynamics, based on individual needs, providing conditions for maximum sports performance. Objective: This study aimed to investigate the cytokine response during different running disciplines' practice and provide quantitative estimates of changes in these markers.